LEVERAGING PODCAST FOR ELT: A SYSTEMATIC REVIEW - Dian Nuriska Cahyanti; Ela Latifah; Nafan Tarihoran (PT Wahana Global Education, 2025)
The rapid development of digital technology has significantly impacted English Language Teaching (ELT), one of which is podcasts, which are an innovative medium that offers an authentic listening experience, flexible access to learning, and encourages student learning independence. Podcasts effectively improve students' listening skills, pronunciation, and speaking fluency. However, their application in academic environments still faces challenges, such as limited access to technology, difficulty understanding various accents, and lack of structured teacher guidance. This study aims to synthesize previous research on the role of podcasts in English language learning at the tertiary level, highlighting the pedagogical benefits, challenges, and best practices in integrating podcasts into the curriculum. The method used was a systematic literature review following PRISMA guidelines, analyzing 20 empirical studies published between 2020 and 2024 and obtained from academic databases such as Google Scholar, Publish or Perish, PubMed, Taylor & Francis Online, and Mendeley. The analysis results show that podcasts can significantly improve students' language skills, especially in listening and speaking, and encourage student motivation and learning independence through exposure to authentic and diverse English materials. However, there are challenges in technological limitations, difficulty in understanding varied accents, and lack of lecturer support in the optimal use of podcasts. Therefore, integrating podcasts in English language learning requires careful planning, institutional support, and the active role of teachers in providing clear directions. Further research needs to be conducted to examine the long-term impact and adjust the application of podcasts to the needs of students from various disciplines.